Coastal land use change and evaluation of ecosystem services value enhancement under the background of Yangtze River protection: Taking Jiangyin coastal areas as an example - Zhang, Shiyu; Jin, Cheng; Pan, Xiaoqing; Wei, Luyao; Shao, Haiyan (Frontiers in Environmental Science, 2023)
Evaluating the ecosystem service value is an important step to promote the sustainable development and the construction of ecological civilization of the Yangtze River Economic Belt, the related research is already very rich. However, they neglect the evaluation of coastal areas and lack the deeper thinking of ecological value. To improve these deficiencies, this study takes the coastal area of Jiangyin as the study area, constructs the evaluation method system of ecosystem service value based on the land use data in 2016 and 2020, explores the temporal and spatial variation characteristics of land use and ecosystem service value in the study area, and analyzes reasons for these changes. The results show that: (1) Cultivated land is the main land type in the coastal area, with an area change rate of -15.89%, forest land increases rapidly, with a growth rate of 281.62%, followed by water area with a growth rate of 55.98%, garden land decreases the most, with a decrease rate of 86.36%, followed by construction land of 62.19%. Land use mainly presents the characteristics of changes from construction land to other land, construction land and green space, and cultivated land to cultivated land, water area and forest land. (2) The net increase of ecosystem service value in the coastal area is 483 million, with a growth rate of 137.27%. Among them, the value of forest land accounts for the largest proportion, with a net increase of 264 million yuan and a growth rate of 109.54%. In terms of single function, flood regulation and storage accounts for the main ecosystem service value, reaching more than 65%, with a net increase of 394 million yuan. (3) In terms of spatial distribution, the ecosystem service value of water conservation, flood regulation and storage has a spatial distribution characteristic of being high in the east and low in the west, while the distribution of ecosystem service value of wind prevention and sand fixation is both high and low in the west. In addition, this study further explores the response mechanism of ecological value to the protection measures along the river and the transformation path.......